If Alpha and beta are the zeros of the poynomial
Attachments:
![](https://hi-static.z-dn.net/files/d52/e7d5ef5e2f97c24feec8815085d3d54d.jpg)
Answers
Answered by
0
Alpha + Beta = -2/3
Alpha × Beta = 1/3
[(1-a) *(1+b)+ (1-b) * (1+a)]/ 1 - ab
= 2(1- ab)/ 1- ab
= 2
Where a = alpha
b = beta
Alpha × Beta = 1/3
[(1-a) *(1+b)+ (1-b) * (1+a)]/ 1 - ab
= 2(1- ab)/ 1- ab
= 2
Where a = alpha
b = beta
dhruv77tayal:
wrong
Answered by
1
Answer:
please mark me as brainlist
Attachments:
![](https://hi-static.z-dn.net/files/df1/64dfd0a6f4d341ec15e4229660190c88.jpg)
Similar questions